Virus-like particle (VLP) Lymphatic Trafficking and Immune Response Generation after Immunization by Different Routes - Cubas, Rafael (2009)
Virus-like particles (VLPs) have gained increasing interest for their use as vaccines due to their repetitive antigenic structure which is capable of efficiently activating the immune system. The efficacy of virus-like particle immunization may lie in its ability to traffic into draining lymph nodes while activating antigen-presenting cells in order to initiate the orchestration of signals required for the development of a robust immune response. Currently, there is no comprehensive study showing the correlation of different VLP vaccination routes to immune outcome. In this study, we took an optical imaging approach to directly visualize the trafficking of SHIV VLPs after immunization by commonly used routes and analyzed the corresponding humoral and cellular immune responses generated. We found that VLPs can easily enter the subcapsular sinus of draining lymph nodes with quantitative differences in the number of lymph node involvement depending on the immunization route used. Intradermal immunization led to the largest level of lymph node involvement for the longest period of time, which correlated with the strongest humoral and cellular immune responses. Flow cytometry analysis from extracted splenocytes showed that intradermal immunization led to the largest population of germinal center and activated B cells which translated into higher antibody levels and antigen-specific CTL responses. Our results indicate that VLPs traffic into lymph nodes upon immunization and can be directly visualized by optical imaging techniques. Intradermal immunization showed improved responses and might be a preferable delivery route to use for viral and cancer immunotherapeutic studies involving VLPs.